FARMER PERCEPTION TO ISPO IN OIL PALM PLANTATION IN WEST JAVA - Ernah Ernah; Apong Sandrawati; Melania Fadillah; Dewi Rengganis; Sudarjat Sudarjat (Universitas Tadulako, 2019)
Palm oil is one of the leading commodities in the world market that contributes to the Indonesian economy. In fulfilling market demand but environmental friendly, the Indonesian government issued a policy of sustainable standards known as the Indonesian Sustainable Palm Oil (ISPO) principle. This study aims to determine the farmers' perception of ISPO in the community of oil palm farmers in West Java. This study designed as qualitative research. The results show that not all standards were sustainable. ISO has been applied to oil palm plantations in West Java. For this reason, government efforts were needed to assist farmers in implementing the ISPO